The COVID-19 pandemic behind bars: Experimental evidence showing higher support for decarceration when framed as risk to correctional staff - Erin J. McCauley (Elsevier, 2022)
This study examined the effect of framing COVID-19 spread in correctional facilities as impacting imprisoned individuals or impacting correctional staff on public support for decarceration. I employed an experiment in the 2021 Empire State Poll (n = 765) in which participants were randomly assigned to a treatment condition, which highlighted information about the number of COVID-19 cases among imprisoned individuals, or a control condition, which highlighted correctional staff instead. Participants reported how supportive or unsupportive they are of releasing imprisoned individuals to curb the spread of COVID-19. Overall, 35% of New Yorkers supported decarceration. A higher percentage of respondents supported decarceration when the impact on correctional staff was highlighted (40%) relative to imprisoned individuals (31%). There was also higher support among non-Hispanic Black (54%) and Hispanic (51%) participants relative to non-Hispanic White (28%) participants. Within racial/ethnic groups support for decarceration was higher when the impact on correctional staff was highlighted among non-Hispanic Whites, Hispanics, and those of another race, but not among non-Hispanic Blacks where support for decarceration was higher when the impact on imprisoned individuals was highlighted. Inferential analysis using log binomial regression found that the association between treatment condition assignment and support for decarceration was not significant. Public health practitioners and policy makers should consider leveraging the higher support associated with concerns over the health and wellbeing of correction staff found among some racial/ethnic groups to fight the COVID-19 pandemic.